2017
DOI: 10.1186/s12875-017-0595-3
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ views on (long-term) prescription and use of problematic and potentially inappropriate medication for oldest-old patients—A qualitative interview study with GPs (CIM-TRIAD study)

Abstract: BackgroundPotentially inappropriate medication (PIM) is defined as medication with uncertain therapeutic effects and/or potential adverse drug reactions outweighing the clinical benefits. The prescription rate of PIM for oldest-old patients is high despite the existence of lists of PIM (e.g. the PRISCUS list) and efforts to raise awareness. This study aims at identifying general practitioners’ views on PIM and aspects affecting the (long-term) use of PIM.MethodsAs part of the CIM-TRIAD study, we conducted semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 46 publications
(92 reference statements)
1
17
1
3
Order By: Relevance
“…Tools to reduce PIMs, such as the PRISCUS list [26], Beers criteria [6], the Screening Tool of Older People's Prescriptions (STOPP) and Screening Tool to Alert to Right Treatment (START) criteria [7], exist, but studies have shown that family physicians do not necessarily use them because of negative views [27]. Although physicians are aware of PIM and polypharmacy [27], medication they consider as potentially inappropriate does not necessarily match established criteria such as the PRISCUS list. Interestingly, only a limited number of medication classes were involved in most PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…Tools to reduce PIMs, such as the PRISCUS list [26], Beers criteria [6], the Screening Tool of Older People's Prescriptions (STOPP) and Screening Tool to Alert to Right Treatment (START) criteria [7], exist, but studies have shown that family physicians do not necessarily use them because of negative views [27]. Although physicians are aware of PIM and polypharmacy [27], medication they consider as potentially inappropriate does not necessarily match established criteria such as the PRISCUS list. Interestingly, only a limited number of medication classes were involved in most PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to conduct interviews of full triads containing all three perspectives. We obtained 52 patient interviews (PIM: n = 27, non-PIM: n = 25), 52 GP interviews (PIM: n = 25, non-PIM: n = 22, others: 5; for results see [ 15 ]), and 48 interviews of significant others of the patients (PIM: n = 24, non-PIM: n = 24). Interviews of the triad were usually conducted separately.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, family physicians might feel compelled to keep the treatment initiated by other specialists, feel they do not have all the information needed to recommend a different treatment or patients might be resistant to change. 28…”
Section: Interpretation Of Resultsmentioning
confidence: 99%